Data‐Driven Simulation of Rapid Flux Enhancement of Energetic Electrons With an Upper‐Band Whistler Burst. Issue 4 (5th April 2021) - Saito, S.; Kurita, S.; Miyoshi, Y.; Kasahara, S.; Yokota, S.; Keika, K.; Hori, T.; Kasahara, Y.; Matsuda, S.; Shoji, M.; Nakamura, S.; Matsuoka, A.; et al.
Abstract: The temporal variation of the energetic electron flux distribution caused by whistler mode chorus waves through the cyclotron resonant interaction provides crucial information on how electrons are accelerated in the Earth's inner magnetosphere. This study employs a data‐driven test‐particle simulation which demonstrates that the rapid change of energetic electron distribution observed by the Arase satellite cannot be simply explained by a quasi‐linear diffusion mechanism, but is essentially caused by nonlinear scattering: the phase trapping and the phase dislocation. In response to upper‐band whistler chorus bursts, multiple nonlinear interactions finally achieve an efficient flux enhancement of electrons on a time scale of the chorus burst. A quasi‐linear diffusion model tends to underestimate the flux enhancement of energetic electrons as compared with a model based on the realistic dynamic frequency spectrum of whistler waves. It is concluded that the nonlinear phase trapping plays an important role in the rapid flux enhancement of energetic electrons observed by Arase. Plain Language Summary: Energetic electrons could be a cause of satellite anomalies affected by electric discharge phenomena on its surface and interior materials. To minimize the anomalies through satellite operation, it is important to forecast the temporal variation of the energetic electron flux along the trajectories of a satellite. One of the causes of the variation of the electron flux is whistler mode waves, which are right‐handed, circularly polarized electromagnetic waves that can resonate with energetic electrons. To understand how the electrons are accelerated in realistic situations, we have performed a data‐driven numerical simulation to demonstrate electron scattering, by importing the observation data of the Arase satellite directly to the simulation. Results of the simulation reproduce the temporal variations of energetic electron flux distributions in burst of whistler mode waves. It is found that the nonlinear scattering contributes to the flux enhancement of energetic electrons. It is confirmed that a quasi‐linear diffusion model, which has been used in general so far, cannot explain such a rapid flux enhancement. We conclude that the nonlinear scattering caused by the whistler burst plays an important role in the rapid flux enhancement of energetic electrons observed by the Arase satellite. Key Points: The data‐driven simulation of rapid flux enhancement has been performed using plasma/particle and wave data obtained by Arase The simulation results reproduce the observed temporal variations of energetic electron flux distributions The nonlinear phase trapping contributes to the flux enhancement of electrons above 20 keV